(untitled) (Global Journal of Medical Research, 2011)
Low back pain is a common debilitating disease with negative effect on productivity. Magnetic resonance imaging (MRI) with its excellent soft tissue contrast and absence of bone artefact is the current modality used in evaluating the possible aetiologies of low back pain. MRI availability in Central Africa is recent, with only two existing machines including the newly installed one in Polyclinic Bonanjo, Douala. Aim : To evaluate lumbo-sacral spine MR images with elucidation of possible causes of low back pain. Methodology : A pioneer prospective study of patients who were referred to Department of Radiology, Polyclinic Bonanjo, Douala, Cameroon for MRI of the lumbo-sacral spine from June –November, 2009 was done. Equipment used was 0.3Tesla Hitachi AIRIS 11. Sagital, coronal and axial images were acquired. When indicated T1W-Gd-DTPA and STIR were adjunctive sequences used. Patients with either claustrophobia or having MRI incompartible medical implants were excluded. Results : 48 Patients with age range 20-79 years with mean age of 49.5 were studied. Males were 29(60.4%) and females were 19 (39.6%). The commonest aetiology of low back pain was disc hernia 16(33.3%) with 62,5% occurring at L4/L5 disc level while 25% was at L5/S1. Gender difference decreases with age. Conclusion : Thus disc herniation is the commonest cause of low back in Cameroon, often accompanied by spondylosis.